2019
DOI: 10.1111/ijd.14541
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiologic features of melasma: a multicentric cross‐sectional study from India

Abstract: Background Though melasma is a common skin condition in India, epidemiological studies are few and geographically confined. The present study was designed to gain insights into factors involved in causation and aggravation of melasma, demographic distribution, clinical presentations, and treatment patterns.Methods A cross-sectional multicentric study was conducted in 10 centers distributed across the four regions of India. Data including demographics, personal and family medical history, triggering and aggrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…Many studies show different patterns according to regional variation, as noted also in the multicentric study by Sarkar et al, in which 42.8% of patients had a malar pattern of melasma, with the east and west regions of India most commonly and the north and south regions having a majority of combination pattern. Studies conducted by KrupaShankar et al and Achar and Rathi found centrofacial melasma was the most common.…”
Section: Discussionmentioning
confidence: 86%
“…Many studies show different patterns according to regional variation, as noted also in the multicentric study by Sarkar et al, in which 42.8% of patients had a malar pattern of melasma, with the east and west regions of India most commonly and the north and south regions having a majority of combination pattern. Studies conducted by KrupaShankar et al and Achar and Rathi found centrofacial melasma was the most common.…”
Section: Discussionmentioning
confidence: 86%
“…Pigmentation is a downstream result of the process of photoageing, vascular changes and resulting inflammatory mediators. 12 Addressing the hyperpigmentation alone will not yield lasting benefits, hence combination therapy addressing photoageing, light protection and melanin pigment is required.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, in particular, immunologic, endocrine, and metabolic changes make pregnant women vulnerable to changes in the skin [ 21 ]. The mean age of onset is 38 years predominantly in women (85%) and of those, 59.2% reported onset during their second trimester of pregnancy and 34.6% reported onset after pregnancy [ 22 ]. This suggests that female hormone variations may be involved in the initial pathogenesis of melasma.…”
Section: Reviewmentioning
confidence: 99%
“…The patients were surveyed and their duration of sun exposure per day was approximated. The estimated exposure time was then compared to the severity of the melasma [ 22 ]. The severity of melasma was determined using the Melasma Area and Severity Index (MASI) which is a universal tool that quantifies the severity based on three factors: area of involvement, darkness, and homogeneity [ 3 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation